2003
DOI: 10.1111/j.1365-2621.2003.tb05772.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Different Honduran Coffees in Relation to Several Environments

Abstract: To better know the cup quality of Honduran coffee, a study was carried out on samples from 52 Arabica coffee plots spread throughout 6 producing regions in Honduras. The aim was to identify environmental and agronomic factors that affect coffee quality. Biochemical and physical characteristics of coffees after roasting were used to link quality descriptors to these variables by means of multiple factor analyses. Coffees of superior quality came from the Olancho and El Paraíso regions. High altitudes and annual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
124
2
9

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(146 citation statements)
references
References 5 publications
5
124
2
9
Order By: Relevance
“…The sensory profiles indicated some sensory attributes were independent of degree of roasting, which confirmed that other factors may be influencing the sensory characteristics of coffee. The origins of coffee, including growing regions and variety of bean, evidently have noticeable impact on the sensory fingerprint of each coffee; this is supported by numerous studies Decazy, Avelino, Guyot, Perriot, Pineda, & Cilas, 2003;Nebesny and Budryn, 2006;Ross, Pecka, & Weller, 2006;Bhumiratana et al, submitted-2010).…”
Section: Descriptive Sensory Datasupporting
confidence: 49%
“…The sensory profiles indicated some sensory attributes were independent of degree of roasting, which confirmed that other factors may be influencing the sensory characteristics of coffee. The origins of coffee, including growing regions and variety of bean, evidently have noticeable impact on the sensory fingerprint of each coffee; this is supported by numerous studies Decazy, Avelino, Guyot, Perriot, Pineda, & Cilas, 2003;Nebesny and Budryn, 2006;Ross, Pecka, & Weller, 2006;Bhumiratana et al, submitted-2010).…”
Section: Descriptive Sensory Datasupporting
confidence: 49%
“…Decazy et al (2003) report that saccharose, which is the sugar present in largest quantities, is degraded during roasting, and is used in Maillard reactions and caramelization, giving origin to various volatile and nonvolatile compounds responsible for the sweet characteristic of coffees. Therefore it is possible to say that there is a tendency that the location of Serra do Boné favors the accumulation of sugars in green coffee, something that is not observed in the other farms.…”
Section: Resultsmentioning
confidence: 99%
“…Fruiting ripening and cup quality: In addition to genetic background (Carvalho, 1988) and harvesting and postharvesting procedures (Clarke, 1985;Vincent, 1985), production of coffee berries with superior beverage quality appears to be highly dependent on the climate conditions (Guyot et al, 1966;Decasy et al, 2003), although little is known as to how such a dependency arises (Njoroge, 1998). The search for good quality beverage has spread the cultivation of coffee to higher altitudes, as observed in southeastern Brazil, and in countries such as Costa Rica, Guatemala and Honduras, where beans are graded by site elevation.…”
Section: Reproductive Growthmentioning
confidence: 99%